Climate Change and Vector-Borne Diseases in Southeast Asia: A Systematic Literature Review - Putri Wulan Akbar; Nur Edy Suminarti; Nisa Arifani (Journal of Islamic Medicine, 2026)
Background: Climate change contributes to the increasing risk of vector-borne diseases by altering environmental conditions that influence vector dynamics and disease transmission patterns. Southeast Asia is a region highly vulnerable to the impacts of climate change while simultaneously bearing a substantial burden of vector-borne diseases. However, scientific evidence that systematically examines the relationship between climatic variables and vector-borne diseases in this region remains limited and fragmented. Objective: This study aims to synthesize the most recent scientific evidence on the relationship between climate change and climate variability and the occurrence of vector-borne diseases in Southeast Asia. Methods: A literature search was conducted in the Scopus, EBSCOhost, and PubMed databases using combinations of keywords related to climate change and vector-borne diseases. Included studies were original research articles published in English between 2021 and 2026 and conducted in Southeast Asian countries. The selection process followed the PRISMA guidelines. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Data synthesis was performed narratively. Results:Seven studies met the inclusion criteria. Temperature exhibited a non-linear relationship with disease risk, whereby increases within an optimal range enhanced transmission, while extreme temperatures tended to exert a protective effect. Absolute humidity and rainfall were generally positively associated with increased incidence, although their effects depended on intensity and temporal distribution. Heatwaves and drought demonstrated delayed effects that may elevate risk, whereas extremely wet conditions showed potential to reduce transmission in certain contexts. Environmental factors also played a significant role: high urban density supported the dominance of specific vectors, and air pollutants demonstrated protective associations in several studies. Conclusion: The relationship between climate variables and vector-borne diseases is complex, non-linear, and context-specific. The integration of extreme climate indicators and environmental factors into early warning systems and area-based control strategies is essential to address the challenges posed by climate change in Southeast Asia.